(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
Annually, 10 million individuals succumb to cancer, with 70% of cancer-related mortalities concentrated in developing nations, Indonesia included. In the year 2020, the documented prevalence of cancer in Indonesia comprised 65,858 cases of mammary neoplasms and 36,633 instances of cervical carcinoma. Despite the etiology of cancer remaining elusive, its mitigation is feasible through proactive screening methodologies, such as the IVA and SADANIS. The primary objective of the initiative is the augmentation of public awareness and cognizance, fostering early detection practices about cervical and mammary malignancies. The implemented methodology integrates didactic sessions elucidating the multifaceted facets of cancer, complemented by the execution of early detection protocols, specifically the IVA and SADANIS procedures. The cohort involved 39 female participants, with the collaborative execution transpiring at the Subdistrict Health Center in conjunction with the Poncol Health Center. Outcome evaluations revealed a suboptimal baseline knowledge quotient amongst participants concerning cancer etiology and preventive measures (96.55%). Noteworthy findings from the Pap smear encompassed a 3.5% positivity rate, whereas the SADANIS revealed a concurrent 3.5% incidence of palpable breast nodules. In light of these findings, the populace must undergo periodic early detection screenings. Moreover, healthcare professionals should perpetuate the augmentation of community awareness through periodic educational interventions, specifically targeting the female demographic. — Setiap tahun 10 juta orang meninggal karena kanker, dimana 70% kematian akibat kanker terjadi di negara berkembang termasuk Indonesia. Tahun 2020, prevalensi kanker di Indonesia sebanyak 65,858 kasus kanker payudara, dan 36,633 kasus kanker leher rahim. Kanker merupakan penyakit yang tidak diketahui penyebabnya secara pasti, namun dapat dicegah dengan screening, yaitu melalui pemeriksaan IVA dan SADANIS. Tujuan dari kegiatan ini meningkatkan pengetahuan dan kesadaran masyarakat untuk melakukan deteksi dini penyakit kanker leher rahim dan kanker payudara. Metode yang digunakan, dengan memberikan edukasi tentang kanker dan melakukan deteksi dini dengan pemeriksaan IVA dan SADANIS. Peserta sejumlah 29 perempuan, kegiatan dilaksanakan di Puskesmas Pembantu Balaikota bekerja sama dengan Puskesmas Poncol. Hasil kegiatan yang dilaksanakan didapatkan pengetahuan peserta tentang kanker dan pencegahannya rendah (96,55%), hasil pemeriksaan IVA ditemukan 3,5% positif dan hasil pemeriksaan SADANIS 3,5% ditemukan terdapat benjolan pada payudaranya. Berdasarkan hasil kegiatan, masyarakat perlu melakukan pemeriksaan deteksi dini secara rutin dan tenaga kesehatan dapat meningkatkan pengetahuan tentang kanker dengan memberikan edukasi secara berkala kepada masyarakat khususnya perempuan.